Captive women : oblivion and memory in Argentina - Rotker, Susana, 1954- (Cultural studies of the Americas, 2002)
Argentina is the only country in the Americas that has successfully erased the presence of Indians, Africans, and mestizos from its national story. Official documents, reports, and censuses have largely omitted any references to the country's non-European inhabitants, mirroring official policies that once included the extermination of indigenous peoples and continued to encourage Europeanization well into the twentieth century. In Captive Women, Susana Rotker exposes this concerted act of forgetting by looking at a historical phenomenon that has been expunged from the national record: the widespread kidnapping of white women by Argentine Indians in the nineteenth century. Captivity narratives form a major part of the early colonial literature of the United States, but Argentina has no such tradition. These narratives contradict Argentina's carefully shaped self-image, one historically based on the absence of aboriginal peoples and the impossibility of miscegenation. Captive Women uses close andimaginative readings of military documents, government treaties, travel journals, essays, and memoirs to explore the foundations of Argentina's strategies of silence and its negation of uncomfortable historical realities.